Surgical profile and management of carpal tunnel syndrome among sample of Iraqi patients attending a teaching hospital - Al-Imari, Amir Naif Kadum; Bakkour, Amine Mohammed; Surriah, Mohammed Hillu; Saaid, Ayaad Makki (International Surgery Journal, 2019)
Background: Carpal tunnel syndrome (CTS) is a common condition that causes pain, numbness, and weakness in the hands and wrist. CTS affecting female more than male, and diagnosed by EMG and NCS. The aim of this study was to describe the profile and surgical management among sample of Iraqi patients. Methods: Sixty-two patients collected from the neuro-surgical departments of the specialized surgical hospital from June 2015 till June 2018, all patients studied thoroughly regarding age, sex, associated diseases, clinical features, EMG studies, surgery and out come and follow up for at least one year. Results: There was around 2:1 female: male, with age predominant between 40-60 years. All the patients had pain (aching) and most of them numbness, and tingling and only 1/3 had atrophy of muscle of the hand all diagnosed by EMG and NCS, treated surgically results were good compared with other studies regarding complications and final outcome. Conclusions: Surgery for CTS is safe and successful surgery under meticulus procedure and appropriate choice of patients.